Perbuatan Melawan Hukum Notaris terhadap Akta Partij Rapat Umum Pemegang Saham (RUPS) dan akta Partij Putusan Sirkuler Pemegang Saham Perseroan Terbatas: (Studi Putusan Nomor 46/PDT.G/2023/PN CBI jo. 236/Pdt.G/2019/PN.Bdg jo. 141/Pdt.G/2018/PN Blb) - Gusnia Hanako; Hasim Purba; Mahmul Siregar (CV Rewang Rencang, 2025)
This study examines the problems in the preparation of circular decision deeds and General Meeting of Shareholders deeds by notaries, particularly related to the lack of notarial neutrality and the failure to incorporate the parties' intentions into the deed, which renders the deed invalid. Using normative legal research methods with qualitative analysis, this study analyzes several court decisions and concludes that in Decision Number 46/PDT.G/2023/PN CBI and 236/Pdt.G/2019/PN.Bdg jo its cassation decision, as well as Decision Number 141/Pdt.G/2018/PN Blb jo its appeal and cassation decisions, the notaries were proven to have committed unlawful acts based on Article 1365 of the Civil Code for violating the Notary Position Law, although the researcher considers the decision in the second case to be inappropriate because the notary had exercised his authority in accordance with regulations by incorporating the parties' intentions into the deed.